Congenital intestinal malrotation, duodenal obstruction combined with dextrocardia: a rare case report - Yan, Jianhong; Yang, Hang; Xiao, Han; Li, Chuanxin (Frontiers in Pediatrics, 2025)
BackgroundBoth intestinal malrotation and situs inversus are usually asymptomatic and extremely rare. We reported a case of congenital intestinal malrotation, duodenal obstruction, dextrocardia, and pancreatic and splenic hypoplasia in a newborn.Case presentationThe patient was a 17-day-old premature infant who had experienced recurrent vomiting for 5 days. Upper gastrointestinal and small intestine contrast imaging indicated intestinal malrotation and duodenal obstruction. Abdominal contrast-enhanced CT showed a small, underdeveloped pancreas, multiple nodular soft tissue densities in the area anterior to the left kidney and posterior to the stomach, and unclear splenic venous and arterial structures. Cardiac CT revealed dextrocardia with an atrial septal defect (secundum type). The laparoscopic Ladd's procedure was performed. The postoperative course was uneventful, and the patient recovered well during a 4-month follow-up.ConclusionsThis patient was very young and presented with multiple abnormalities. This case highlights the importance of early diagnosis, timely referral, and management of such rare congenital anomalies to achieve favorable outcomes.